2016
DOI: 10.11591/edulearn.v10i2.3430
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reading Skills on Students’ Performance in Science and Mathematics in Public and Private Secondary Schools

Abstract: In the Philippine education system, reading, mathematics, and science formed part of the core areas of basic education curriculum. For the last decade, the quality of Philippine education was put into a big question due to poor performance of students in mathematics and science tests both local and abroad. The initial result of current efforts of the government by adopting K-12 curriculum didn't do much to change the status quo. The purpose of this study is to determine the reading predictors of students' perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 7 publications
(6 reference statements)
0
22
0
Order By: Relevance
“…There are some findings which suggest a direct relationship between reading comprehension and solving the word problems (Pape, 2004;Vilenius-Tuohimaa, Aunola, & Nurmi, 2008). Nonetheless, some studies reveal that such a relationship is not statistically significant (r=0.162, p>.05; Imam, Abas-Mastura & Jamil, 2013;Imam, 2016). Reading comprehension also calls for high-level cognitive skills so as to be able to support understanding the text (Yuill & Oakhill, 1991).…”
Section: H2: Logical Reasoning Positively Affects Reading Comprehensimentioning
confidence: 99%
See 1 more Smart Citation
“…There are some findings which suggest a direct relationship between reading comprehension and solving the word problems (Pape, 2004;Vilenius-Tuohimaa, Aunola, & Nurmi, 2008). Nonetheless, some studies reveal that such a relationship is not statistically significant (r=0.162, p>.05; Imam, Abas-Mastura & Jamil, 2013;Imam, 2016). Reading comprehension also calls for high-level cognitive skills so as to be able to support understanding the text (Yuill & Oakhill, 1991).…”
Section: H2: Logical Reasoning Positively Affects Reading Comprehensimentioning
confidence: 99%
“…The findings suggest that reading comprehension has a significant role in mathematical performance (Pape, 2004;Vilenius-Tuohimaa, Aunola & Nurmi, 2008). However, although there are also studies indicating that there is a positive and significant relationship between reading skills and mathematics performance, it is also reported that this relationship is not statistically significant (r = 0.162, p> .05) (Imam, Abas-Mastura & Jamil, 2013;Imam, 2016). Due to such inconclusive findings, more studies examining the relationship between reading comprehension and word problem-solving performance will contribute to the literature.…”
Section: Introductionmentioning
confidence: 95%
“…Hanemann (2015) clearly defined reading literacy as a foundation skill which stimulates lifelong learning and relates to successful academic achievement. Imam (2016) also deeply highlighted the benefit of reading skill in helping children develop their numeracy, science and literacy skills. With reading skill, the children can then effortlessly acquire language skills such as listening, writing and speaking (Kennedy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Reading is believed to be a reflective, analytical, and critical skill, leading to the development of other fields of ability such as math or science. The ability to read is related to the ability of mathematics and science ( [4], [5]).…”
Section: Introductionmentioning
confidence: 99%